Sistem Kendali Take-Off Quadcopter Ar.Drone Menggunakan Logika Fuzzy - Fajar Miftakhul Ula; Gembong Edhi Setyawan; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Unmanned Aerial Vehicle (UAV) or we knownby plane without crew is type of sky's robot explores have incrase develop in nowadays. One kinds of UAV is quadcopter, quadcopter is kinds of sky robots have four motors as vane drive. On process make quadcopter have many trouble, that is experienced pilot requirements for fly quadcopter use remote, expecially for the take-off, because take-off on quadcopter is absolute phase to keep the stability. So need have auto pilot system to manage process a great take-off. Based on that trouble so made experiment about guide system of take-off quadcopter use fuzzy logic with rule 7x7 where have two input is acceleration and change of acceleration, while output which result is speed. For know the error phase is examination as much as ten times with high 1 - 4 meter. And for know time need quadcopter for get hover use record time with stopwatch. So the result of this experiment is the precision obtained is already good but the time if takes is still need a long time while the rule is match with result output.